Does low alcohol use increase the risk of sickness absence? A discordant twin study. (December 2016) - Østby, Kristian; Czajkowski, Nikolai; Knudsen, Gun; Ystrøm, Eivind; Gjerde, Line; Kendler, Kenneth; Ørstavik, Ragnhild; Reichborn-Kjennerud, Ted
Abstract Background Results from observational studies suggest that people who drink little or no alcohol are less healthy than medium drinkers. This has been demonstrated for many different measures of health, including sick leave. However, whether these associations are causal or due to confounding remains to be clarified. The aim of this study was to use a discordant twin design to determine whether the increased level of sick leave associated with a low level of alcohol consumption, as compared to those with a medium level of consumption, reflects a causal mechanism or is due to genetic or environmental confounding. Methods Six thousand seven hundred thirty-four young adult twins from the Norwegian Institute of Public Health's twin panel were in 1998 assessed for frequency of alcohol use and binge drinking. Data were linked to the Norwegian National Insurance Administration's recordings of sick leave over a 10 year period. The associations between alcohol consumption and sick leave were first estimated in the total study population, and then within di- and monozygotic twin pairs discordant for alcohol use. Results Compared to medium consumption, both low and high alcohol consumption was associated with increased risk of sick leave. When low level drinkers were compared to medium level drinkers in a discordant twin design, the results were consistent with the association being due to genetic confounding rather than a causal effect. Conclusions The increased level of sick leave observed with low level drinkers seems to be mainly explained by confounding from genetic factors. In all observational studies of the relationship between alcohol consumption and health, one should be aware that important genetic confounders are likely to influence the results.